A leading-edge scenario in the phylogeography and evolutionary history of East Asian insular Taxus in Taiwan and the Philippines - Kuo, Hao-Chih; Schoneman, Travis; Gao, Lian-Ming; Gruezo, William Sm.; Amoroso, Victor B.; Yang, Yang; Yang, Kuo-Cheng; Chien, Ching-Te; Möller, Michael; Wang, Chun-Neng (Frontiers in Genetics, 2024)
The cool temperate origin of gymnosperm Taxus species in East Asia are especially diverse and widespread. Certain lineages have managed to extend their distribution further south to subtropical and tropical islands such as Taiwan and Philippines. To address questions including whether these insular lineages, recently identified as T. phytonii, have become genetically distinct from each other and from their continental relatives, and when and how they colonized their residing islands, we sampled over totally 11 populations, covering 179 Taxus individuals from Taiwan and the Philippines. Using four cpDNA and one nuclear marker, we showed in population genetic and genealogical analyses that the two insular lineages were genetically distinct from each other and also from other continental Taxus and that they represented each other's closest relative. Estimated with the coalescent-based MTT (MultiTypeTree) analyses, we inferred an origin of Taiwan T. phytonii more ancient than 2.49 Mya, and that of Philippine T. phytonii more ancient than 1.08 Mya. In addition, the divergence demographic history revealed by both MTT and IM (isolation with migration) analyses indicated the presence of recent post-split migrations from a continental taxon, T. mairei, to Taiwan T. phytonii, as well as from Taiwan T. phytonii to Philippine T. phytonii. Overall, this study suggests Taiwan as a stepping stone through which the temperateorigin yew trees can extend their distributions to tropical regions such as the Philippines.